Negative optical absorption and up-energy conversion in dendrites of nanostructured silver grafted with α/β-poly(vinylidene fluoride) in small hierarchical structures. (April 2018) - Phule, A.D.; Ram, S.; Shinde, S.K.; Choi, J.H.; Tyagi, A.K.
Abstract: We report that a negative optical absorption arises in a sharp band at 325 nm (energy hν2 ) in a nanostructured silver (n-Ag) doped poly(vinylidene fluoride) (PVF2 ) in a hybrid nanocomposite of films (∼100 μm thickness). Two polymorphs α- and β-PVF2 are co-stretched through the n-Ag crystallites in dendrites of hierarchical structures. A critical 0.5 wt% n-Ag dosage promotes this band of extinction coefficient to be enhanced by as much as 2.009 × 10 3, i.e. a 30% value in the Ag-surface plasmon band 350–650 nm (hν1 ). An electron donor Ag (4d 10 5s 1 ) bonds to an electron accepter moiety CF2 of PVF2, it tunes a dielectric field and sets up an up-energy conversion of the plasmon band. The FESEM and HRTEM images reveal fcc-Ag dendrites entangled with in-built PVF2 surface layers (2–3 nm thickness). The IR phonon bands show how a α → β-PVF2 transformation propagates onto a nascent n-Ag surface and how it is raised-up in small steps of 0.1 wt% and up to 5.0 wt%. In a model scheme, we illustrate how a rigid core-shell of a capsule conducts a new transfer mechanism of the energy to a cold surface plasmon (core) in a coherent collision, so as to balance a net value hν2 = h( ν 3 − ν 1 ). It absorbs light in a weak band at 210 nm (hν3 ) in a π → π* electron transition in the CC bonds of the PVF2 (shell), and results in a negative absorption in a coherent excitation of the energy-carriers. A light-emitter on absorption over a wide range of wavelengths (200–650 nm) offers a unique type of energy-converter. Graphical abstract: Image 1 Highlights: ● UV–visible light-energy conversion in films of n-Ag doped PVF2 in dendrites. ● The n-Ag anchors α → β-PVF2 in small dendrites and hierarchical clusters, which plays a crucial role in finely tuning the optical, dielectric and other properties in a hybrid n-Ag:PVF2 phase with stable metal-polymer interfaces. ● A microscopic phase α → β PVF2 turns-up and it bonds to the n-Ag at its coherent facets and stretches via the n-Ag in dendrites and hierarchical structures. ● The IR phonon bands show how a α → β-PVF2 transformation propagates onto a nascent n-Ag surface, and it is raised-up in small steps of 0.1 wt% and up to 5.0 wt%. ● Uniquely, a strongly negative optical absorption occurs over 270–350 nm in hot LSPs-Ag on an interband transition 4d 10 5s 1 → 4d 9 5s 1 p 1 n-Ag via π → π* (PVF2 ) electronic absorption.